Evaluation of the physical and mechanical properties of paricá wood (Schizolobium amazonicum) used in the plywood industry in the State of Maranhão - de Sousa Lima, Vinicius; Lima Nascimento, Sandriel; Almeida dos Santos, Jéssica; da Cruz Rodrigues, Ednilson; Lucio Meneses Nascimento, Bruno; Dione Araújo Cunha, Rita; Fabio Caesar, Sandro; Miguel Santos Dias, João (Seven Editora, 2023)
Paricá (Schizolobium amazonicum) is a species native to the Amazon region, whose physical and mechanical characteristics are the basis of the acceptance of this species by the timber market, especially through its use for the production of plywood panels and parallel blade panels (LVL). The objective of this work was to evaluate the physical and mechanical properties of paricá wood used in the plywood industry in the State of Maranhão. Moisture content, apparent and basic densities, volumetric variation, parallel and perpendicular compressive strengths to the total, shear strength parallel to the total, bending strength and elasticity modules to the compression parallel to the total and flexion were analyzed. The plot of wood analyzed presented moisture content in air balance (11.33%), low apparent density (275.57 kg.m-3) and reduced volumetric variation (8.75%), and these properties were below the values presented by the bibliography for woods of similar ages. The mechanical properties analyzed (compressive strength parallel to the great, normal compressive strength to the great, modulus of rupture in the flexion, modulus of elasticity in flexion, shear strength parallel to the great and modulus of elasticity to the compression parallel to the great) also presented values lower than the average of the results obtained in the bibliography. Thus, the use of paricá wood in plywood panels is a valid alternative, considering that they are light and stable with regard to dimensional variation, when compared with products from eucalyptus wood. However, it is pertinent to carry out actions aimed at improving the mechanical properties of paricá wood, in order to increase the properties of strength and stiffness. DOI: https://doi.org/10.56238/tfisdwv1-041